1994
DOI: 10.1093/oxfordjournals.aje.a116921
|View full text |Cite
|
Sign up to set email alerts
|

Vegetables, Fruit, and Colon Cancer in the lowa Women's Health Study

Abstract: Previous epidemiologic studies have shown an inverse association between vegetable and fruit consumption and colon cancer risk; few of these studies have been prospective or have focused on women. This report describes results from a prospective cohort study of 41,837 women aged 55-69 years who completed a 127-item food frequency questionnaire in 1986 and were monitored for cancer incidence for 5 years via the State Health Registry of Iowa. After specific exclusion criteria were applied, 212 colon cancer cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
200
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(209 citation statements)
references
References 0 publications
6
200
2
1
Order By: Relevance
“…A meta-analysis of 37 observational epidemiologic studbasis for a qualitative interaction. 14 In another meta-analysis of 19 case-control studies, 37 it was found females) as fructose, as did the consumption of simple sugar (OR Å 0.70 for males and 1.32 for females). To that grain fiber or cereal intake was either unrelated or positively associated with colon carcinoma risk.…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis of 37 observational epidemiologic studbasis for a qualitative interaction. 14 In another meta-analysis of 19 case-control studies, 37 it was found females) as fructose, as did the consumption of simple sugar (OR Å 0.70 for males and 1.32 for females). To that grain fiber or cereal intake was either unrelated or positively associated with colon carcinoma risk.…”
Section: Discussionmentioning
confidence: 97%
“…A 1992 meta-analysis of casecontrol studies supported this hypothesis (Howe et al, 1992), but a later re-analysis of these data, considering study heterogeneity and limited to studies with validated diet assessment instruments, did not support a role for fiber (Friedenreich et al, 1994). Most prospective cohort studies of dietary fiber and colon cancer risk have not supported an association (Heilbrun et al, 1985;Willett et al, 1990;Giovannucci et al, 1994;Steinmetz et al, 1994;Kato et al, 1997;Fuchs et al, 1999;Pietinen et al, 1999;Terry et al, 2001a;. However, a recent large European study involving 10 countries found a 25% lower risk of colon cancer associated with higher fiber intakes compared to low intakes (Bingham et al, 2003a).…”
Section: Fibermentioning
confidence: 99%
“…Meta-analyses of case-control studies suggested, on average, a 50% reduction in the risk of development of CRC between the 2 groups. However, the published large prospective cohort studies showed equivocal findings [68,69,70], with the largest published study analyzing data on a study population of 19,541 with 16 years of follow-up showing no protective effect of dietary fibre against the development of CRC (RR = 1.08, 95% CI = 0.9–1.29) [71]. Similar findings were also obtained rom another trial using 958 subjects with 36 months of follow-up (RR = 1.00, 95% CI = 0.9–1.12).…”
Section: Chemoprevention In Practicementioning
confidence: 99%